Sistem Informasi Aplikasi Penyewaan Lapangan Futsal pada Tons Futsal Berbasis Web - Yulianti, Yulianti; Mulyati, Sri; Al'Gani, Adam Lutfi; Suhartono, Ismi; Triananda, Guntur Chandra; Ramadani, Ramadani (Jurnal Informatika Universitas Pamulang, 2022)
In Tons Futsal, the information system for reserving pitches is still manual. Reservations made on the field in handwriting. Calculations and proof of payment continue to rely on a large amount of paper or books to generate payment reports, so to summarize, the data manager faces challenges because there is a large amount of paper to collect, as well as no organized storage of bookings data that makes proper and accurate use of the futsal field, allowing data to be lost. The goal of this research is to contribute to the improvement of the files ordering and data processing processes on Tons futsal. The interview technique, system analysis, system design, implementation, and maintenance of the software are all employed in this process. It is believed that the findings of this research will help managers and customers overcome common roadblocks and improve their efficiency and effectiveness.